منهج القرآن الكريم في بيان خطوات الشيطان - نبيل محمد مرعي, سعيد (University of Eloued جامعة الوادي, 2019)
ناول الباحث في هذه الدراسة الحديث عن منهج القرآن في بيان خطوات الشيطان، وقد بدأ بتعريف مصطلحات البحث (المنهج، والخطوات، والشيطان)، ثم تناول معالم منهج القرآن في التحذير من اتباع خطوات الشيطان، الأول منها: تمام الهداية، والدخول في الإسلام كافة، والثاني: تحقق التزكية، والثالث: الولاء لله، والرابع: العلم، كما تناول الباحث منهج القرآن في بيان خطوات الشيطان، وجعلها مرتبة وفق ثلاث مراحل، كما يلي: المرحلة الأولى: الإزلال، وفيها: النزغ، والوسوسة، والهمزات، والمس، والافتان، والاستحواذ، والمرحلة الثانية: الإضلال، وفيها: الهوى، والتزيين، والاقتران، والولاية، والمرحلة الثالثة: الشيطنة، وفيها الوحي والتنزيل، وفق منهج الاستقراء والتحليل لمعاني الكلمات الواردة في الآيات التي تحدثت عن عمل الشيطان، متوصلاً إلى ترتيب اجتهادي من وجهة نظر الباحث هو الأقرب للصواب، والله أعلم. The Approach of the Holy Qur'an in Stating the Steps of Satan: View and Study Abstract: The study discusses the approach of the Qur'an in stating the steps of the devil or Satan. It starts with defining the terms of the research (approach, steps, and Satan), and then deals with the features of the Quran's approach in warning against following the steps of the Satan. These features include complete guidance, establishing purification, loyalty to Allah, and seeking knowledge. The research also shows the Qur'anic approach in arranging the Satanic steps as follows: an evil suggestion, insinuation, temptations, devil's touch, provocation, appropriation, prejudice, being a companionship, loyalty, and revelation. This arrangement is based on using method of induction and analysis of the words mentioned in the verse talking about the Satan's work, as the researcher believes this is a valid way to be arranged .
عرض ودراسة
مقال بمجلة الشهاب
Keywords: منهج القرآن ; خطوات الشيطان